2020
DOI: 10.3390/nano10112141
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Synthesis of Novel Amorphous TiO2 Nanorods Decorated rGO Hybrid Composites with Wide Band Microwave Absorption

Abstract: Amorphous structures may play important roles in achieving highly efficient microwave absorption performance due to the polarization losses induced by the disorders, vacancies and other functional groups existed in them. Herein, a kind of amorphous TiO2/rGO composite (a-TiO2/rGO) was successfully fabricated via a facile one-step solvothermal method. The complex permittivity of the composites can be regulated by adjusting the addition of precursor solution. The minimum reflection loss of a-TiO2/rGO composites r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…To investigate the MA properties of the prepared RGO/h-TiO 2nw composites, reflection loss (RL) values are calculated on the basis of relative complex permittivity ( ε r = ε ′ − jε ′′) and relative complex permeability ( μ r = μ ′ − jμ ′′) at a given frequency and absorber thickness according to the transmit line theory: 46 where Z 0 is the impedance of free space, Z in is the input impedance of the absorber, f is the frequency of the microwave, d is the thickness of the absorber, and c is the velocity of light. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the MA properties of the prepared RGO/h-TiO 2nw composites, reflection loss (RL) values are calculated on the basis of relative complex permittivity ( ε r = ε ′ − jε ′′) and relative complex permeability ( μ r = μ ′ − jμ ′′) at a given frequency and absorber thickness according to the transmit line theory: 46 where Z 0 is the impedance of free space, Z in is the input impedance of the absorber, f is the frequency of the microwave, d is the thickness of the absorber, and c is the velocity of light. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RGO/h-TiO 2nw composites synthesized in this study, outperform all other reported materials with outstanding RL values and ultralow filler contents in the paraffin matrix, and are accompanied by a broad EAB. 9,18,24,28,31,38,43,46,51–55…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 b, c) are also consistent with this viewpoint. At present, most researchists have agreed that the conductivity of the sample is closely related to the crystal structure and morphology of materials [ 82 86 ]. In this case, the crystal structure of CNC is almost amorphous (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to explore multiple loss mechanisms in Ni 3 S 2 @NSGA-650, the curves of ε" versus ε were plotted in Figure 6d. The curve can be easily divided into two parts-one is a straight line with larger ε related to the conduction loss, which mainly stems from the migration of electrons in a 3D interconnected network structure [22,23]; the other is several semicircles with smaller ε with respect to the polarization loss [32,33]. The multiple polarization relaxations in Ni 3 S 2 @NSGA-650 include the dipolar polarizations at the defect and functional groups on the N, S-codoped rGO skeleton, and heterogeneous interfacial polarizations among Ni 3 S 2 nanoparticles and graphene sheets.…”
Section: Em Absorption Performance Of Ni 3 S 2 @N S-codoped Graphene ...mentioning
confidence: 99%